Sustained-Release Nanocapsules Enable Long-Lasting Stabilization of Li Anode for Practical Li-Metal Batteries - Liu, Qianqian; Xu, Yifei; Wang, Jianghao; Zhao, Bo; Li, Zijian; Wu, Hao Bin (Nano-Micro Letters, 2020)
A robust solid-electrolyte interphase (SEI) enabled by electrolyte additive is a promising approach to stabilize Li anode and improve Li cycling efficiency. However, the self-sacrificial nature of SEI forming additives limits their capability to stabilize Li anode for long-term cycling. Herein, we demonstrate nanocapsules made from metal–organic frameworks for sustained release of LiNO3 as surface passivation additive in commercial carbonate-based electrolyte. The nanocapsules can offer over 10 times more LiNO3 than the solubility of LiNO3. Continuous supply of LiNO3 by nanocapsules forms a nitride-rich SEI layer on Li anode and persistently remedies SEI during prolonged cycling. As a result, lifespan of thin Li anode in 50 μm, which experiences drastic volume change and repeated SEI formation during cycling, has been notably improved. By pairing with an industry-level thick LiCoO2 cathode, practical Li-metal full cell demonstrates a remarkable capacity retention of 90% after 240 cycles, in contrast to fast capacity drop after 60 cycles in LiNO3 saturated electrolyte. Highlights: 1 Nanocapsules made from metal–organic frameworks were designed for sustained release of additive (LiNO3) to passivate Li anode in commercial carbonate-based electrolyte. 2 The nanocapsules with continuous supply of LiNO3 formed a nitride-rich solid electrolyte interphase layer on Li anode and persistently remedied the interphase during prolonged cycling. 3 The practical Li-metal full cell delivered a prolonged lifespan with 90% capacity retention after 240 cycles which has been hardly achieved in commercial electrolyte.